THE CLINICAL IMPORTANCE OF ERYTHROCYTE PHENOTYPING IN THE ABO AND RHD SYSTEMS (REMUNOM, 2026)
Considering that transfusion safety directly depends on donor–recipient compatibility, this study addressed the need to understand the clinical importance of erythrocyte phenotyping within the ABO and RhD systems. Objective: To identify the main deterministic factors that demonstrate the relevance of this practice as an essential tool for preventing alloimmunization and adverse transfusion reactions. Methodology: An integrative literature review with comparative analysis of the findings is carried out, based on articles published between 2020 and 2025 in the SciELO and PubMed databases. Results: Seventeen studies were selected, revealing that the systematic application of erythrocyte phenotyping significantly reduces the risk of incompatibilities, improves blood stock management, and strengthens hemovigilance policies. Conclusion: Erythrocyte phenotyping is an indispensable tool for transfusion safety and for achieving more precise, ethical, and humanized clinical practice.